2007
DOI: 10.1002/ar.20558
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Shape Analysis of Differences in the Shape of the Corpus Callosum Between Genders

Abstract: Sexual dimorphic characteristics, which play an important role in human evolution studies and biological research, can be studied morphologically and metrically. Geometric morphometrics allows a better assessment of morphological characteristics. Statistical shape analysis has a long history in neuroanatomical and other research. The aim of this study was to identify shape differences of the corpus callosum between genders. Landmark coordinate data were collected from two-dimensional magnetic resonance imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 33 publications
(55 reference statements)
0
38
0
1
Order By: Relevance
“…The first report suggesting a possible sex effect on CC morphology was published in 1982 18 and described the splenium as being more prominent in female adults. Since that report, many studies have focused on that particular point and could not find any sex differences in the splenium size in adults 19,20 or children. 10,21 Our results are in keeping with these findings.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The first report suggesting a possible sex effect on CC morphology was published in 1982 18 and described the splenium as being more prominent in female adults. Since that report, many studies have focused on that particular point and could not find any sex differences in the splenium size in adults 19,20 or children. 10,21 Our results are in keeping with these findings.…”
Section: Discussionmentioning
confidence: 96%
“…10,15 Distances measured between different landmarks identified on the CC have also been evaluated. 19 These techniques are useful for a better understanding of CC growth and variations, but their main drawback is that they are not at all easy to use in daily practice. Therefore, we favored linear easily reproducible measurements.…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports [11][12][13][14][15][16][17][18] on the morphological gender difference of the corpus callosum. The gender difference of the corpus callosum was first suggested by DeLacosteUtamsing and Holloway [11], who found that adult human women had a larger splenium.…”
Section: Discussionmentioning
confidence: 98%
“…However, there are very few studies about analysis of hand- writing by statistical shape analysis. [15][16][17][18][19] Only Arslan and Guney examined shape changes between characters written by left-handed and righthanded persons and females and males. 20 The novelty of this study is due to rarity of handwriting analysis in patients with MS, followup of MS patients for one year, and use of statistical shape analysis for handwriting analysis.…”
Section: Discussionmentioning
confidence: 99%